New Developments in the Ultrasonography Diagnosis of Gallbladder Diseases - Lara Mencarini; Amanda Vestito; Rocco Maurizio Zagari; Marco Montagnani (Gastroenterology Insights, 2024)
Gallbladder diseases are very common, and their diagnosis is based on clinical–laboratory evaluation and imaging techniques. Considering the different imaging diagnostic tools, ultrasound (US) has the advantage of high accuracy combined with easy availability. Therefore, when a gallbladder disease is suspected, US can readily assist the clinician in the medical office or the emergency department. The high performance of US in the diagnosis of gallbladder diseases is mainly related to its anatomic location. The most frequent gallbladder pathological condition is gallstones disease, easily diagnosed via US examination. Acute cholecystitis (AC), a possible complication of gallstone disease, can be readily recognized due to its specific sonographic features. Additionally, a number of benign, borderline or malignant gallbladder lesions may be detected via US evaluation. The combined use of standard B-mode US and additional sonographic techniques, such as contrast-enhanced ultrasonography (CEUS), may provide a more detailed study of gallbladder lesions. Multiparametric US (combination of multiple sonographic tools) can improve the diagnostic yield during gallbladder examination.